GRN, NOTCH3, FN1, and PINK1 expression in eutopic endometrium: potential biomarkers in the detection of endometriosis - a pilot study - Holzer, Isabell; Machado Weber, Amanda; Marshall, Anne; Freis, Alexander; Jauckus, Julia; Strowitzki, Thomas; Germeyer, Ariane (Journal of assisted reproduction and genetics, 2020)
Endometriosis (EM) is a common gynecological disease affecting 10-15% of women of reproductive age. However, molecular mechanisms and pathogenesis are still not completely understood. Furthermore, due to the absence of a reliable clinical biomarker, the only viable method for the often-delayed definitive diagnosis is laparoscopic surgery. Our objective was to analyze molecular differences of selected endometrial proteins and genes of women suffering from different stages of EM compared with healthy women to evaluate potential clinical biomarkers.
Gesehen am 31.08.2021